Pharmacogenetics and the system of biotransformation of drugs - Eleshov, D.Z.; Pogosyan, G.P.; Hovhannissyan, R.G. (KSU publ., 2017)
In this article the state and prospects of one of the modern directions of personalized medicine — pharmacogenetics are examined. General ideas about the role of biotransformation and metabolism of medicinal substances in pharmacogenetics were given, namely information on the polymorphism of genes involved in biotransformation of drugs and in the genetic control of their interaction, the description of the enzymes of the I and II phases of biotransformation of drugs.The first phase undergo oxidation, reduction and hydrolysis reactions in order to increase the polarity of the compound is described. In this phase, induction or inhibition by enzymes P450 is the main mechanism of drug interactions. The crystal structure of cytochrome P450 is studied. The main processes of the second phase of biotransformation are described: glucuronation, sulfation, conjugation with glycine, conjugation with glutathione, acetylation, methylation. Pathways of metabolism, enzymes involved in them, biotransformation phases are considered. The role of UDF-glucuronyltransferases in the transformation of drugs in the human body is shown. The classification of the superfamily of the UGT gene is described, the products of the members of this superfamily are described. The possibilities of genotyping using real-time PCR for the detection of individual single nucleotide polymorphisms, determination of the number of copies of the gene, pyrosequencing, mass spectrometry, matrix-activated laser desorption / ionization, and the use of microchips. The problems of drug use, such as drug toxicity, side effects, etc. are considered. Examples are given of the study of the effect of drugs on organisms in different countries. Such problems of genomic testing in our country as lack of funding, lack of clear cooperation between industrial and scientific circles, lack of specialists, creation of concrete and comprehensive.
Дəрілік заттардың биоөзгеріс жүйесі жəне фармакогенетикасысы
Фармакогенетика и система биотрансформации лекарств
Keywords: pharmacogenetics; cytochrome P450 isoenzymes; allele; UDF-glucuronyltransferase; polymorphic genes; genotypes; real-time PCR; LC marker; ferments of metabolism; gene expression